Biotechnology Research in the CGIAR - Concept Note - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2013)
This study is designed to provide the CGIAR system, the CGIAR Research Programs, and Donors with an analysis and recommendations for enhancing biotechnology research, through investment and partnership strategies that can best serve system efficiency and the attainment of CGIAR goals. It focuses on genomics and bioinformatics, and GMOs, including the related policy and institutional aspects.